Situating Vocational Education in Social Science University: A case-study of best practices in VET (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2023)
Vocational education in India has gained prominence in India in last decade. Investment by International organisations like World Bank, OECD and Government initiatives on Skilling India has resulted in formalising and modernising Vocational Education and Training (VET) in India (Pilz. M. & Regel. J., 2021). In the National Education Policy (NEP) 2020, an emphasis is laid on re-imagining vocational education in India and makes it sought after domain with the larger formal education system. The NEP 2020 also emphasises the need to bring vocational education at par with other school subject by making it appealing and job-ready for students. In an attempt to mainstream vocational education in University space, AUD (a social science University) launched School of Vocational Studies (SVS) in 2017. SVS was set up to provide full-time or part-time tertiary education opportunities to high school graduates of Delhi and other neighbouring states. Three batches have graduated from SVS in three verticals- BVoc in Tourism and Hospitality, B Voc. in Retail Management and BVoc in Early Childhood Centre Management Entrepreneurship. SVS's location in a social science or liberal University space has provided it a unique character where the aim of Vocational Education and Training (as laid out by UGC and NEP2020) meets with AUD's vision of humanistic education. This article discusses the best practices of SVS and how is it becoming a sought after programme within Delhi Vocational Education and Training chapter. The empirical part of the article describes a comprehensive view of best practices as shared by graduated students (n=160) and teachers (n=30). The article elaborates on the best practices in five themes- uniqueness about the programme, curriculum design and process, pedagogical practices, assessment policy and University support to the student. The article concludes that students and teachers valued the pedagogy and the internship model followed at SVS the most, followed by soft skill training. The article can help Academicians and VET training institutes to re-imagine VET and make it more humane for aspiring students.